The impact of climate change and firm characteristics on the financial performance of agro firm : study on Malaysian public listed companies - Hossain, Nazmul (2018)
The aim this study is to examine the impacts of climate change and firm characteristics on Malaysian agro firm performance. The sample of this study consists of 33 Malaysian public listed plantation firms with 462 firm year observations for the period of 2003 to 2016. Panel data regressions such as the pooled OLS, fixed effect and random effect model are used to analyse the dataset. Based on the regression results, growth opportunity, rainfall and El Nino positively and significantly impact ROA, whereby leverage, liquidity, temperature and flood negatively and significantly impact ROA. Another measure of firm performance which is ROE are positively and significantly influenced by liquidity, growth opportunity and El Nino. However, temperature and flood negatively and significantly impact ROE. At the same time, leverage, temperature and flood positively and significantly foster Tobin’s Q where firm size negatively and significantly impacts Tobin’s Q. Overall, all variables are significant with firm performance accept firm age is found to be insignificant in influencing Malaysian agro firm performance.